Asymptotic behavior of the solutions of second-order differential equations with rapidly varying nonlinearities - Evtukhov, V. M.; Chernikova, A. G.; Евтухов, В. М.; Черникова, А. Г.; Евтухов, В. М.; Черникова, А. Г. (Institute of Mathematics, NAS of Ukraine, 2017)
We establish conditions for the existence of one class of solutions of two-term nonautonomous differential equations of the second-order with rapidly varying nonlinearities and the asymptotic representations for these solutions and their first-order derivatives as и $t \uparrow ω (ω ≤ +∞ )$.